Influence of the polysaccharide addition method on the properties of fresh mortars. (April 2015) - Poinot, Thomas; Bartholin, Marie-Claude; Govin, Alexandre; Grosseau, Philippe
Abstract: This study focused on comparison of polysaccharide addition methods, either in powder form, or as a solute in the mixing water. The influence of the methods was assessed by measuring water retention and rheological properties with one cellulose ether and two guar ethers. Polysaccharides were more efficient to enhance water retention and rheological properties when they are pre-dissolved in the mixing water. This is related to differences in polymer concentration in the pore solution of mortar. These differences are not stemming from a difference in dissolution kinetics, but from a difference in adsorption on growing hydrates. Being immediately available when it is pre-dissolved, the admixture slows down the nucleation and growth of hydrates limiting in turn the surface area for further adsorption. Consequently, more molecules are left in the interstitial solution and a lower dosage is required to achieve the overlapping of polymer coils, responsible for the effectiveness of polysaccharides.